2017
DOI: 10.1093/eurpub/ckx175
|View full text |Cite
|
Sign up to set email alerts
|

Europeanization process impacts the patterns of alcohol consumption in the Western Balkans

Abstract: Our analysis provides useful evidence about the possible influence of Europeanization process especially on spirits consumption levels in Western Balkans. These findings draw attention to the need to implement new policies in order to prevent alcohol health-related harm due to the possible increase of wine and beer consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…From demographic and data about habits within the study sample we could see that smoking, drinking alcohol and coffee were widespread and could have influenced the study participants’ perception of HRQoL. Although the process of Europeanization is taking place in countries of Western Balkans, and has already led to a decrease in alcohol consumption ( 22 , 23 ), these habits are still following patterns from the past and making up one of the target population’s important specifics, further stressing the need for region-specific instruments for measuring HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…From demographic and data about habits within the study sample we could see that smoking, drinking alcohol and coffee were widespread and could have influenced the study participants’ perception of HRQoL. Although the process of Europeanization is taking place in countries of Western Balkans, and has already led to a decrease in alcohol consumption ( 22 , 23 ), these habits are still following patterns from the past and making up one of the target population’s important specifics, further stressing the need for region-specific instruments for measuring HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal level addresses local policies [19]. We used this model previously to assess the influence of the Europeanization process on alcohol consumption in the WB [20]. We adapted the model for population health suggested by Huynen et al [19], as indicated in Figs.…”
Section: Conceptual Frameworkmentioning
confidence: 99%